French Cinema and the Integration of Young Women Actors of Maghrebi Heritage. Issue 3 (December 2015) - Tarr, Carrie
Abstract : Since the turn of the century, three young female actors of Maghrebi heritage have achieved the award of Most Promising Newcomer (Meilleur espoir féminin) at the French film industry's annual César ceremonies: Rachida Krim in 2002 for her performance in Coline Serreau's Chaos (2001), Hafsia Herzi in 2008 for her performance in Abdellatif Kechiche's La Graine et le mulet/Couscous (2007), and Leïla Bekhti in 2011 for her performance in Tout ce qui brille/All That Glitters (2010), directed by Géraldine Nakache and Hervé Mimran. On the assumption that this award may be indicative of the growing visibility of Maghrebi-French female actors at the centre of the French film industry, this article traces the career trajectories of these three actors and their contribution to representations of gender, ethnicity and identity in contemporary multi-ethnic postcolonial France from their award-winning roles through to their most recent performances, both in France and in a transnational context.